Design research through practice : from the lab, field, and showroom - Koskinen, Ilpo Kalevi (Morgan Kaufmann, 2011)
Businesses and the HCI and Interaction Design communities have embraced design and design research. Design research as a field blends methodologies from several disciplines - sociology, engineering, software, philosophy, industrial design, HCI/interaction design -- so designers can learn from past successes and failure and don't have to reinvent the wheel for each new design (whether it's a digital product, a building, an airplane or furniture). They take into account form, function, and, ultimately, users. Many books exist in the research and academic realm for this field, but none create a usable bridge to design practice. Although business people are embracing design, they are not going to become designers. Design researchers need tools to apply their research in the real world. Design Research through Practice takes advanced design practice as its starting point, but enriches it to build a design process than can respond to both academic and practical problems. The aims of the book are to study three design research traditions that cover methodological directions in current leading research community. Taking you from the Lab, Field and to the Showroom, Ilpo Koskinen and his group of researchers show you successful traditions in design research that have been integrated into processes and products. Bridging the gap from design research to design practice, this is a must have for any designer. . Gathers design research experts from traditional lab science, social science, art, industrial design, UX and HCI to lend tested practices and how they can be used in a variety of design projects . Provides a multidisciplinary story of the whole design process, with proven and teachable techniques that can solve both academic and practical problems . Presents key examples illustrating how research is applied and vignettes summarizing the key how-to details of specific projects.